ENHANCING ENGLISH LANGUAGE LEARNING THROUGH THE INTEGRATION OF INFORMATION TECHNOLOGY (Konferensiyalar | Conferences, 2024)
In today's digital age, the integration of Information Technology (IT) has revolutionized the field of education, particularly in the teaching of English as a second language. This article explores the various ways in which IT can be effectively utilized to enhance English language learning outcomes. By leveraging the power of technology, educators can create engaging and interactive learning experiences that cater to the diverse needs of students. This article discusses the benefits of incorporating IT tools such as language learning apps, online resources, virtual classrooms, and AI-powered chatbots in English language teaching. Additionally, it highlights the challenges and considerations that educators need to address when integrating IT into their teaching practices.